Respiratory Abnormalities among Occupationally Exposed, Non-Smoking Brick Kiln Workers from Punjab,India - Tandon, Supriya (Int J Occup Environ Med, 2017)
BACKGROUND: Brick manufacturing industry is one of the oldest and fast-growing industries in India that employs a large section of people. Brick kiln workers are occupationally exposed to air pollutants. Nonetheless, only a few studies have so far been conducted on their respiratory health. OBJECTIVE: To investigate the extent of respiratory impairment in brick kiln workers and to correlate it with the duration of exposure. METHODS: A cross-sectional study was conducted. Spirometric parameters of 110 non-smoking male brick kiln workers aged 18–35 years in Patiala district, Punjab, India, were compared with an age-matched comparison group of 90 unexposed individuals. RESULTS: Brick kiln workers showed a significant (p<0.05) decline in forced expiratory volume in 1 second (FEV(1)), forced vital capacity (FVC), forced mid-expiratory flow rate (FEF(25-75%)) and peak expiratory flow rate (PEFR) compared with those of the comparison group. The extent of deterioration in lung function of brick kiln workers was associated with the duration of exposure. In workers with >8 years of exposure, the mean values of FEV(1) (1.92 L), FVC (2.01 L), FEF(25-75%) (2.19 L/s) and PEFR (4.81 L/s) were significantly (p<0.05) lower than those recorded in workers with <8 years of exposure in whom the values were 2.01 L, 2.68 L, 2.71 L/s, and 5.76 L/s, respectively. CONCLUSION: There is a significant association between exposure to workplace pollutants and lung function deterioration among brick kiln workers.